2022
DOI: 10.1177/1087724x221112958
|View full text |Cite
|
Sign up to set email alerts
|

The Scourge of Orphaned and Abandoned Wells: Leveraging Public-Private-Citizen Collaboration to Solve a Big Problem

Abstract: Orphaned and abandoned wells are emblematic of the challenges of abandoned infrastructure. With over 2.5 million idle wells in the United States, this is a large problem that requires engagement across the public, private, non-profit, and civic sectors. This article conducts a focused case study on orphaned and abandoned well reclamation in Pennsylvania. Elite interviews, government document review, and scholarly literature reveal the barriers to effective collaboration across the sectors, but also substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Risk reduction could include raising awareness of the issue in Michigan (and across other states where numerous aging dams also exist). This way they can play their role in civil society to pressure legislatures to invest in either xing or removing these aging dams-civil society groups have had some success in capping abandoned oil and gas wells, which are somewhat similar to idled dams (Mallinson et al 2023). Research on other dangerous infrastructure (such as nuclear plants) suggests that people close to these plants tend to downplay the dangers, and that the dangers disproportionately affect the less powerful in society.…”
Section: Discussionmentioning
confidence: 99%
“…Risk reduction could include raising awareness of the issue in Michigan (and across other states where numerous aging dams also exist). This way they can play their role in civil society to pressure legislatures to invest in either xing or removing these aging dams-civil society groups have had some success in capping abandoned oil and gas wells, which are somewhat similar to idled dams (Mallinson et al 2023). Research on other dangerous infrastructure (such as nuclear plants) suggests that people close to these plants tend to downplay the dangers, and that the dangers disproportionately affect the less powerful in society.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that the level of trust is not always the same throughout the collaboration process (J. Li, 2023;Mallinson et al, 2023).…”
Section: Antecedentsmentioning
confidence: 99%